CULTURA DE SEGURANÇA DOS ALIMENTOS: COMPREENSÃO DAS AUTORIDADES SANITÁRIAS EM PROCESSO DE CATEGORIZAÇÃO - Corte , Letícia Ferrigolo Dalla (2024)
The food safety culture (FSC) is a crucial phenomenon that contributes to ensuring that the production, distribution, and consumption of food are carried out safely, being recognized as a significant risk factor for the occurrence of foodborne disease outbreaks. In this study, the objective is to evaluate the understanding of FSC among health authorities involved in the categorization of food services, as well as to characterize the sociodemographic and educational profile of these health authorities, qualify them regarding FSC, and identify changes in their understanding of FSC after qualification. This is a qualitative and descriptive study, in which the profile of the health surveillance authorities (VISA) in the central region of the state of Rio Grande do Sul (RS) was surveyed through a questionnaire, and two focus groups (FG), before and after FSC qualification, were conducted. The study included health authorities directly involved in municipalities in the central region of Rio Grande do Sul. This study was approved by the Ethics Committee of the Franciscan University, with opinion number 5.828.021. Of the 24 health authorities from 10 municipalities in the central region of the state, 54% were women and 46% were men, with an average age of 43 years, and over 70% have completed higher education. However, among them, the courses that stand out the most are pharmacy, veterinary medicine, environmental engineering, administration, accounting, social assistance, and only one authority has a degree in nutrition. Of the total participants, 66% had already participated in food safety training, and of these, only 12% (2 authorities) conduct annual training. It is observed that the vast majority do not undergo periodic training and capacity building, a contradiction concerning Brazilian legislation. In the qualitative analysis before and after qualification, the coding system was used. In the first stage, before the qualification of health authorities, it was observed in the inductive analysis of the cores of meaning, the need to create 3 subcategories for the elaboration of the main category "Causes and actors involved in foodborne disease outbreak". In contrast, after qualification, there was no need for subcategories, but the final result was the same main category. Health authorities had a low perception of FSC, as observed in the profile analysis prior to qualification. This may indicate a lack of understanding or appreciation of the importance of FSC in the context of food safety. After qualification, in the statements of health authorities, the elements of FSC became more evident, thus suggesting that the qualification provided a deeper understanding or a renewed assessment of the contribution of FSC to food safety. The study revealed that some health authorities had a limited understanding of FSC and its related practices during the profile analysis. Before qualification, this understanding was superficial; however, after training, there was a noticeable improvement. The statements of the authorities post-qualification evidenced the identification of FSC elements, indicating an increase in awareness and application of food safety principles. Given the presented results, further studies focusing on profiling VISA and qualifying these authorities regarding FSC are necessary to improve educational efforts targeted at this audience. Additionally, the interaction between academia and public sectors, which facilitated the exchange of experiences, was fundamental for the professional development of both researchers and the research's target audience.